Two Venovenous Extracorporeal Membrane Oxygenation for One Gunshot - Louis Pot; Alizée Porto; Audrey Le Saux; Amandine Bichon; Emi Cauchois; Marc Gainnier; Julien Carvelli; Jeremy Bourenne (Case Reports in Critical Care)
Venovenous extracorporeal membrane oxygenation (VV-ECMO) is an adjuvant treatment for severe acute respiratory distress syndrome (ARDS) with refractory hypoxemia. Contraindications to therapeutic anticoagulation must be ruled out prior to ECMO implementation. We report the case of a 17-year-old male admitted in intensive care unit (ICU) for penetrating chest trauma due to multiple gunshot wounds. The body computed tomography (body CT scan) documented right pulmonary contusions and a homolateral hemothorax. His condition rapidly deteriorated with refractory hypoxemia due to lung contusion requiring invasive mechanical ventilation (IMV) and polytransfused hemorrhagic shock. During his stay in ICU, venovenous ECMO (VV-ECMO) was implemented twice, firstly for trauma-induced ARDS and secondly after thoracic surgery. This case emphasizes the successful use of VV-ECMO in posttraumatic ARDS without increasing the risk of bleeding.